Dampak Relokasi Pasar Tradisional Terhadap Kondisi Sosial Ekonomi Pedagang di Pasar Kertosono Kabupaten Nganjuk - Ermita Yusida; Frada Nadya Megatara Putra; Hadi Sumarsono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
This study aims to determine traders' responses regarding the relocation policy of Kertosono Market, accessibility to the Kertosono Market before and after relocation, the impact of the relocation of Kertosono Market social-economic conditions of traders. This research is quantitative descriptive. The population in this study were all traders who sell at Kertosono Market. The results showed that 83.07% of respondents did not agree with the relocation. Accessibility to Kertosono Market before and after relocation was 63.07% of the respondents' residences were> 1 km away before relocation, 55.38% were> 1 km out after relocation. The impact of relocating Kertosono Market on the social-economic conditions was 92.30% of respondents were comfortable selling, 7.69% encountered problems, 96.92% were able to advance, and after relocation, namely 84.61% of respondents were uncomfortable when selling, 15.38% found no issues, 92.30% were unable to progress. After relocation, the economic condition of traders increased by 81.53% in the very low classification, decreasing 33.84% in the high category. Therefore, capital assistance for small traders is very much needed. So, in addition to providing capital assistance, the government should also offer training in the form of financial planning and digital marketing so that traders can expand their business. In the future, there needs to be a particular study regarding the comparison of traders in traditional markets and modern markets.